On universalism in connection with the interpretation of magic in the semiotics of Juri Lotman - Lepik, Peet (Sign Systems Studies, 2002)
The article examines the first phase of the universalistic interpretations in Juri Lotman’s semiotics, which is characterized by holism and maximalism derived from the Saussurean cultural concept. There is an analysis of Juri Lotman’s 1967 lecture, previously unpublished, where universal status is accorded to text functions (including magic functions). Such an approach is a substantial revision of the Saussurean understandings of the relationship between language and speech. This interpretation of magic is compared with the examination of the same concept in Juri Lotman’s 1981 article “Contract and self-sacrifice as archetypical cultural models”, which substantially contradicts the concept developed in his 1967 lecture. Both these magic models produce a number of objections, and apparently seem to bear the deforming traces of their respective universalistic theoretical schema.